Sosialisasi Pengelolaan dan Pemanfaatan Sampah Organik Rumah Tangga Dalam Memproduksi Ekoenzim - Nurliah Nurliah; Salma Elika; Uni W. Sagena (Sekolah Tinggi Ekonomi Bisnis Syariah Bina Mandiri, 2022)
The increase in the amount of waste per day increases along with human needs as consumption creatures so that it becomes a problem that can cause various problems. So the reduction of organic waste must be managed with a breakthrough that is easy and cheap and provides many benefits. One solution is to process waste into eco-enzymes. Ecoenzymes are considered the right solution because the raw materials can be easily obtained and cheap. Through the fermentation process for three months, the eco-enzyme was able to obtain a very nutritious solution. Starting as a cleaning fluid and watering plants. In addition to being environmentally friendly, the results of household organic waste management are also of economic value, because the manufacturing costs are not expensive and can be used by the community both for personal use and for sale. The method of implementing this service uses training with lecture methods and offline questions and answers using media presentations in front of residents of Keli Village, Woha District, Bima Regency and direct practice of making ecoenzymes by field extension workers. The practice of making ecoenzymes mentored by field extension workers and assisted by KKN Unmul shows that the community is able to apply ecoenzyme manufacture to process household organic waste. This service shows results with the addition of skills and knowledge in implementing ecoenzyme manufacture in reducing household waste by the community.